Novel [(3-indolylmethylene)hydrazono]indolin-2-ones as apoptotic anti-proliferative agents: design, synthesis and in vitro biological evaluation - Wagdy M. Eldehna; Mahmoud F. Abo-Ashour; Hany S. Ibrahim; Ghada H. Al-Ansary; Hazem A. Ghabbour; Mahmoud M. Elaasser; Hanaa Y. A. Ahmed; Nesreen A. Safwat (Taylor & Francis Group, 2018)
On account of their significance as apoptosis inducing agents, merging indole and 3-hydrazinoindolin-2-one scaffolds is a logic tactic for designing pro-apoptotic agents. Consequently, 27 hybrids (6a-r, 9a-f and 11a-c) were synthesised and evaluated for their cytotoxicity against MCF-7, HepG-2 and HCT-116 cancer cell lines. SAR studies unravelled that N-propylindole derivatives were the most active compounds such as 6n (MCF-7; IC50=1.04 µM), which displayed a significant decrease of cell population in the G2/M phase and significant increase in the early and late apoptosis by 19-folds in Annexin-V-FTIC assay. Also, 6n increased the expression of caspase-3, caspase-9, cytochrome C and Bax and decreased the expression of Bcl-2. Moreover, compounds 6i, 6j, 6n and 6q generated ROS by significant increase in the level of SOD and depletion of the levels of CAT and GSH-Px in MCF-7.